ANALISIS PENURUNAN TANAH LUNAK TERHADAP PERKERASAN JALAN KAKU MENGGUNAKAN METODE ELEMEN HINGGA (Studi Kasus: Jalan Srijaya Raya, Kota Palembang) - Nurul Fadhilah; Lindung Zalbuin Mase; Hardiansyah Hardiansyah; Rena Misliniyati; Khairul Amri (Matriks Teknik Sipil, 2025)
Rigid pavement is a commonly used pavement in soft subgrade conditions because it can anticipate soil subsidence in the transverse and longitudinal directions of the roadway as a result of uneven load distribution due to inhomogeneous soil. Road pavement that is passed by excessive loads will cause the road to experience soil subsidence which will also affect the soil layer below so that research on the problem is needed. This research uses the finite element method which aims to determine the vertical settlement of soil (Uy), the maximum settlement of 3650 days, and the safety factor (Msf) that occurs in soft soil layers against rigid pavement on Srijaya Raya road, Palembang City. The soil characteristics on Srijaya Raya Road are dominated by clay soil with low to medium plasticity which is dominantly soft so that it can cause significant road damage if maintenance is not carried out. Based on the research, it was found that the maximum subsidence value of the distributed load was at STA 0 + 806 at point BH-02 located at the Air Waru Bridge towards Indralaya, which was -0.04847 m with a safety factor of 1.650 and the maximum subsidence for 3650 days was at STA 2 + 103 at point BH-04 located at the Air Kenanga Bridge towards Palembang of -0.539 m.Keywords: finite element method; rigid pavement; safety factor; settlement.